The Influence of Iranian Immigrant Shiites on the Development of Interpretive Studies of the Holy Quran During the rule of the Deccan Shiite states (1098 - 895 AH) - Sayyed Hashem Misavy (قرآن فرهنگ و تمدن, 2021)
The Holy Quran in the early years of the arrival of Islam in the land of India as the most important Islamic principle and model was considered by the Muslims of these areas. In the meantime, the migration of Iranian Shiite commentators had a favorable and fundamental effect on the scientific development of the course of interpretive studies, and their first attempt was made to dynamize and acquaint the inhabitants of this land with Quranic teachings and interpretation of divine verses. The peak of Shiite activity in this field is related to the formation of the Deccan Shiite states (1098-895 AH), which Iranians by passing through the stage of evolution (1 – 6 AH) entered the stage of developing interpretation (7 - 12 AH). During this period, the presence of a large number of Iranian Shiites and the support of the Deccan Shiite rulers for them led to the development and expansion of Shiite activities in religious matters related to the interpretive teachings of the Holy Quran. The present article, with a descriptive-analytical approach and based on primary source historical library studies, seeks to answer the question of how the migration of Iranian Shiites to the Deccan region led to the expansion of interpretive studies of the Holy Quran in these areas. The hypothesis is that the Iranian immigrant Shiites, by organizing interpretation classes and writing books related to this subject, had a great impact on expanding the familiarity of the inhabitants of these areas with the interpretive teachings of the Holy Quran. The results of the research indicate that the Iranian immigrant Shiites, considering the familiarity of the residents of Deccan areas with the Persian language and the support of the Deccan Shiite rulers for them; By forming interpretive classes, they made the residents of these areas more familiar with issues related to the Holy Quran. Also, Iranians have written commentary books and the residents of Deccan have access to these books; They helped them strengthen their understanding of Qur'anic subjects.